Analisis SWOT dalam Pengembangan Bisnis (Studi pada Sentra Jenang di Desa Kaliputu Kudus) - Istiqomah, Istiqomah; Andriyanto, Irsad (BISNIS, 2017)
The rapid business competition encourages every company to have a sharp strategy in order to excel in competing with its competitors or at least able to stay afloat to run its business. This study aims to analyze opportunities and business development at Sentra Jenang in Kaliputu Kudus Tourism Village. Respondents of this research are entrepreneurs who are located in Sentra Jenang Tourism Village kaliputu Kudus. The research data obtained by observation and interview is analyzed descriptively by using SWOT strategy matrix to analyze the strategy specified by the respondents. The results of this study indicate that there are some problems faced by some small entrepreneurs that are difficult to develop due to not have a place to market their products, the quality of human resources that are poorly trained to inhibit the production process, the company does not have good financial management so that difficulty for the management of funds, with increasingly fierce competition. The competition that arises more on jenang products from outside Kaliputu and the inclusion of substitution products that other snacks are more modern and follow the development of the era. From the threats that exist then every MSME or jenang industry in the tourist village of Kaliputu Kudus should make innovations of new variants in order to compete in the market and not inferior to other products.